Motivation and Action (Springer International Publishing, 2018)
This third edition provides translations of all chapters of the most recent fifth German edition of Motivation and Action, including several entirely new chapters. It provides comprehensive coverage of the history of motivation, and introduces up-to-date theories and new research findings. Early sections provide a broad introduction to, and deep understanding of, the field of motivation psychology, mapping out different perspectives and research traditions. Subsequent chapters examine major themes of human motivation, including achievement, affiliation, and power motivation as well as the fundamentals of motivation psychology, such as motivated and goal oriented behaviors, implicit and explicit motives, and the regulation of development. In addition, the book discusses the roles of motivation in three practical fields: school and college, the workplace, and sports. Topics featured in this text include: Social Relationships and its effects on sexual or intimacy motivation. Conscious and unconscious motivators of behavior. Drives and incentives in the fields of achievement, intimacy, sociability and power. How the biochemistry and structures of our brain shapes motivated behavior. How to engage in intentional goal-directed behavior. The potential and limits of motivation and self-direction in shaping our lives. Motivation and Action, Third Edition, is a must-have resource for undergraduate and graduate students as well as researchers in the fields of motivation psychology, cognitive psychology, and social psychology, as well as personality psychology and agency. About the Editor: Jutta Heckhausen is the daughter of Heinz Heckhausen, who published "Motivation and Action" as a monograph in 1980 and who died in 1988 just before the 2nd edition came out. Dr. Heckhausen received her Ph.D. in 1985 from the University of Strathclyde, Glasgow with a dissertation about early mother-child interaction, and did her Habilitation in 1996 at the Free University of Berlin with a monograph about developmental regulation in adulthood. Dr. Heckhausen worked for many years at the Max Planck Institute for Human Development in Berlin, conducting research about the role of motivation in lifespan development. She is currently a professor of psychology at the University of California, Irvine. .